Effect of water temperature on the hydrolysis of two absorbable sutures used in fish surgery - Sarah A. Cannizzo; Simon C. Roe; Craig A. Harms; Michael K. Stoskopf (Canadian Science Publishing, 2016)
Persistence of absorbable sutures in fishes in waters below 10 °C affects surgical decisions including approach, closure strategy, and suture selection. We hypothesized that the rate of suture hydrolysis would vary directly with water temperature. Two absorbable monofilament 3-0 suture materials used in fish surgery, poliglecaprone (Monocryl™) and polyglyconate (Maxon™), were evaluated. The maximum tensile load (strength) was measured for suture loops (n = 6) maintained in filtered city water for 2, 4, 6, or 8 weeks at 4, 25, or 37 °C. For Maxon™ at 4 or 25 °C, tensile strength did not decrease over time. However, for Monocryl™ at 4 °C, 2-, 4-, and 8-week loops were stronger than baseline loops. At 25 °C, tensile strength of the suture material declined after 2 weeks. Also, at 37 °C, the optimal design temperature for both suture materials, the strength of Maxon™ decreased at 6 and 8 weeks. Two 4-week loops of Monocryl™ disintegrated when handled, and after 6 and 8 weeks, all were untestable. This study confirms that absorbable sutures lose strength more slowly at ambient temperatures lower than the optimal design temperature (e.g., human body temperature) and will likely be retained longer in fishes living in waters below 25 °C.